Use of semi-finished cherry-beet puree in technology of sweet dishes and desserts - Ushchapovskyi, Artem; Ivchuk, Nadiya (My University, 2020)
Sweet dishes and desserts are in high demand among consumers. However, these products usually have an unbalanced chemical composition, high caloric content, high fat and carbohydrate content, relatively low protein content and insufficient amount of biologically active substances. The source of natural biologically active substances (BAS) are purees, juices, extracts, decoctions of fruits, vegetables, cultivated and wild berries, medicinal herbs and more. Therefore, the current issue for this type of product is to improve the recipe of the existing range of sweet dishes through the use of natural plant components of high biological value. Thus, the object of research is the technology of health dessert based on semi-finished cherry-beetroot puree and its influence on the structural-mechanical, physico-chemical and organoleptic characteristics of finished products. The work uses standard research methods in accordance with the requirements of regulatory documentation. The study of betanin content is carried out using spectrophotometric method. Antioxidant activity is determined by the bromine coulometric method. Organoleptic and physicochemical indicators of the finished dish are determined in accordance with DSTU 3718:2007 «Sweet foods, jellies, mousses, puddings, milk concentrates». To enrich sweet dishes and desserts in the creation of health and functional foods, it is proposed to use a semi-finished puree, which includes cherry puree and beetroot puree (ratio 2:1). The possibility of improving the organoleptic, physicochemical and structural-mechanical parameters of finished products through the use of a composite combination of semi-finished cherry-beetroot puree and gelatin in the amount of 3 %. The technology of health dessert has been developed, its quality has been studied according to organoleptic and physicochemical parameters, content of biologically active and nutrients. The presence of a significant amount of biologically active substances that have antioxidant properties, provide health and preventive effect of dessert. The developed dessert is recommended for production in restaurants.
Keywords: sweet dishes; health product; semi-finished cherry-beetroot puree; biologically active substances; organoleptic indicators; physical and chemical indicators; кафедра готельно-ресторанної справи; кафедра технології оздоровчих продуктів